1981
DOI: 10.1007/bf01991464
|View full text |Cite
|
Sign up to set email alerts
|

IgG receptors on the mast cell

Abstract: Antisera to the IgG subclasses, 1, 2a, 2b, and 2c, induced histamine release from mast cells obtained from the peritoneal washings of Lister hooded rats. The maximum responses obtained with anti-IgG1 and anti-IgG2a were as great as that for anti-IgE (more than 60% histamine release). Cells from unresponsive Wistar rats which did not secrete appreciable amounts of histamine in response to any of the antisera, produced on active sensitization with ovalbumin a small but significant response on challenge with anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…As there are reports of IgG-mediated release of anaphylactic mediators like histamine and SRS-A from rat peritoneal mast cells (Moodley & Mongar, 1981) and guinea-pig lung in vitro (Andersson & Bergstrand, 1981;Forsberg & Sorenby, 1981), it seems reasonable to assume the release of histamine and SRS-A induced by IgG antibodies in the present investigation to be derived from mast cells. There are indications of separate receptors for IgG and IgE antibodies on mice mast cells (Daeron, ProuvostDanon & Voisin, 1980).…”
Section: Resultsmentioning
confidence: 74%
“…As there are reports of IgG-mediated release of anaphylactic mediators like histamine and SRS-A from rat peritoneal mast cells (Moodley & Mongar, 1981) and guinea-pig lung in vitro (Andersson & Bergstrand, 1981;Forsberg & Sorenby, 1981), it seems reasonable to assume the release of histamine and SRS-A induced by IgG antibodies in the present investigation to be derived from mast cells. There are indications of separate receptors for IgG and IgE antibodies on mice mast cells (Daeron, ProuvostDanon & Voisin, 1980).…”
Section: Resultsmentioning
confidence: 74%
“…These results indicate a high degree of cross-reactivity between and within the hamster and rat immunoglobulins but prevent determination of the nature of the antibody involved in the release process. Since both IgG or IgE a f 0 * 0 may sensitize the mast cell for mediator release (for references see Moodley & Mongar, 1981) either or both antibodies may be implicated in the present response. Consistently, rat peritoneal cells also reacted to both anti-hamster serum and to anti-rat IgE.…”
Section: Discussionmentioning
confidence: 97%
“…There are reports indicating different receptors for IgG and IgE mast cells (Daeron, Pronovost-Danon & Voisin, 1980;Moodley & Morgar 1981). Andersson (1980a) showed that much higher provocation doses must be used to induce a bronchial response in guinea-pigs sensitized according to procedure (b) compared with those sensitized according to procedure (a).…”
Section: Discussionmentioning
confidence: 99%